Past-Year Abuse and Eating Disorder Symptoms Among U.S. College Students - Hazzard, Vivienne M. (Journal of interpersonal violence, 2022)
Evidence consistently indicates associations between eating disorders (EDs) and childhood emotional, physical, and sexual abuse, but the relationship between EDs and abuse occurring later in development has largely been unexplored. Therefore, the objective of this study was to examine associations between past-year abuse and ED symptoms among college students. Participants represented 12 U.S. colleges and universities participating in the Healthy Bodies Study (HBS) between 2013 and 2015 (N = 10,204; Mage = 23.38 years). Students self-reported experiences of emotional, physical, and sexual abuse over the past year. Cognitive ED symptoms (i.e., dietary restraint, shape/weight overvaluation, body dissatisfaction) were measured via the Short-Eating Disorder Examination-Questionnaire (S-EDE-Q), and behavioral ED symptoms (i.e., binge eating, purging) were measured via items from the full EDE-Q. Regression models that adjusted for demographics and weight status were conducted to examine associations between past-year abuse and ED symptoms. Past-year emotional, physical, and sexual abuse each exhibited independent associations with ED symptoms. When mutually adjusting for emotional, physical, and sexual abuse, past-year emotional abuse was associated with higher levels of dietary restraint (b = 0.20, p = .02), shape/weight overvaluation (b = 0.85, p < .001), body dissatisfaction (b = 0.63, p < .001), binge eating (prevalence ratio [PR] = 1.23, p = .002), and purging (PR = 1.68, p < .001), and past-year sexual abuse was associated with shape/weight overvaluation (b = 0.35, p = .03) and purging (PR = 1.71, p = .009) but no other ED symptoms. No associations were observed for past-year physical abuse in mutually adjusted models. In summary, past-year emotional abuse emerged as a key correlate of all ED symptoms examined in this sample of U.S. college students, while past-year sexual abuse also emerged as a key correlate of shape/weight overvaluation and purging. Findings emphasize the need to screen for abuse and implement abuse prevention efforts on college campuses.